Tumor calcinosis. Review of a case and the literature - Rubiano, Jaime; Pérez, María Victoria (Colombia Medica, 1988)
We've come across the first case of tumor calcinosis, described in the Colombian and Latin American literature, and the current literature has been reviewed. We're dealing with a tumor-like entity that calcifies soft tissues and whose cause is likely to be a congenital abnormality in the phosphaturic effect of the parathormone. Biochemically, it is characterized by normal calcium levels and a tendency to high phosphorus levels. It has a characteristic radiological and histological picture. The etiological treatment would be based on phosphorus-binding antacids such as aluminum hydroxide. Surgery plays a palliative role by dying up incapacitating and painful masses. Its frequency is very low. Only 150 cases have been described in the literature.